Recent Developments in Carbon Fibers and Carbon Nanotube-Based Fibers - A Review - Nitilaksha, Hirematha; Jimmy, Maysbc; Gajanan, Bhata
Carbon fibers is a very vast topic to discuss in a limited space such as this review paper. Nevertheless, we herein attempt to provide a succinct summary of current research in carbon fibers (CF), especially carbon nanotube (CNT)based CFs. Brief introduction to CFs with respect to precursors, characterization techniques and applications is presented. Following discussion on different commercially used CF precursors, is a description of the latest new precursors being researched. While finding new low-cost precursors has been a focus of recent research, large scale production of CFs from these new materials is not being realized at the present time. CNTs have received a great deal of attention due to their unique structure and properties. So CNTs and CNT-based CFs or carbon yarns (CYs)are discussed. In addition to providing a brief overview of different methods of providing CNTs, physical and electronic properties of CNTs are discussed. Major focus of this review is CNT based composite fibers. Efforts by several researchers have shown that incorporation of CNTs in carbon fibers is a challenging task, and only a small percent could be introduced successfully. Applications of CFs in various sectors such as the airline industry, sporting industries, and automotive industries are discussed. Applications of CNTs, focusing on composite materials, coatings and films, microelectronics, energy applications and biotechnology are briefly reviewed. Some statistics of world market of CFs as well as future prospects are discussed.
Keywords: CARBON FIBERS; POLYACRYLONITRILE (PAN); PITCH; GRAPHENE OXIDE; LIGNIN; STABILIZATION; CARBON NANOTUBES; NEW PRECURSORS; CNT APPLICATIONS; COMPOSITE FIBERS; CURRENT TRENDS AND FUTURE PROSPECTS OF CARBON FIBERS